New Methods of Aerial Observations on Sea Ice (Nove Methody Morskikh Ledovykh Avyanablyudenii) - Betin,V. V.; Zhadrinskii,S. V.; Uralov,N. S. (1962)
The article discusses a newly introduced semi-instrumental method of observations on sea and continental ice from aircraft by the use of an aerial angle-measuring perspectograph (perspective measuring instrument). The method was successfully used during the last three years in aerial ice reconnaissance over the Baltic Sea. The application of the perspectograph yields dependable and comparable data relative to ice conditions, including the determination of the location of ice in the sea. The method makes possible not only the measurements of areal and linear characteristics of ice but also its thickness, direction and speed of drift, elevation of ice formations over the sea surface, etc. (Author) Trans. of Gosudarstvennyi Okeanograficheskii Institut. Trudy (USSR) n37 p205-230 1959, by M. Slessers. Also available as TT-62-33569.